DEVELOPMENT OF HERBAL CAPSULES CONTAINING MULBERRY LEAF AND BLACK TEA EXTRACTS USING THE MODIFIED LIQUISOLID TECHNIQUES - Noppharat, Kansuphak; Jaipakdee, Napaphak; Limpongsa, Ekapol (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to develop the capsules containing mulberry leaf extract (MLE) and black tea extract (BTE). Methods: MLE and BTE were prepared by maceration and determined for phytochemicals, in vitro alpha-amylase and alpha-glucosidase inhibitory activities using the enzymatic colorimetric assay. The granules of MLE and BTE were prepared by the application of liquisolid technique and evaluated for the flow properties. The selected granule formulation was filled into the hard gelatin capsule and evaluated for weight variation and disintegration. Results: The yields of MLE and BTE solid extracts were 8.12 and 4.23% w/w, respectively. Total phenolic and total flavonoid contents were 32.46±5.22 mg TAE/g DW and 44.03±3.37 mg QE/g DW for MLE and 244.66±23.28 mg TAE/g DW and 214.43±3.22 mg QE/g DW for BTE, respectively. The IC50 for alpha-amylase of MLE and BTE were 0.69±0.04 and 3.34±0.08 mg/ml, respectively; whereas those for alpha-glucosidase of MLE and BTE were 0.67±0.42 and 0.43±0.15 mg/ml, respectively. The granule prepared with MCC and silica at the ratio of 20:1 showed the highest flowability. The weight variation of the prepared MLE and BTE capsules was within the range of the limitation criteria of ±5%. The average disintegration time of capsules was 1.1±0.1 min. Conclusion: Herbal capsules of MLE and BTE were successfully prepared. The suitable carrier and coating were MCC and silica with a ratio of 20:1. This study revealed the potential application of liquisolid technique as a tool to produce a capsule of herbal crude extracts.